NUTRITIONAL APPROACHES IN FOOD INTOLERANCES - Eren, Aslı Gül; Güneş Bayır, Ayşe; GÜNEŞ BAYIR, AYŞE (My University, 2022)
Food intolerance, which is one of the health problems and has become easier to diagnose with the development of modern diagnostic tests, is a non-immunological disorder that occurs as a result of the inability of individuals to digest or absorb a certain food or food component. The prevalence of the disease is 15-20% in the population. Food intolerance symptoms usually appear within half an hour to 48 hours after consuming the food. The most common symptoms are indigestion, headache, diarrhea, vomiting, constipation, diarrhea, abdominal pain, insomnia, fatigue, and urticaria. Although there is no definitive treatment for food intolerances, an important treatment method is to eliminate the food caused by the intolerance from the diet or to allow consuming it in the amount which the body to tolerate. In addition, it has been determined in studies that the complaints of patients are reduced at a high rate by making and applying an individual nutrition plan. In recent years, fermentable short-chain carbohydrate (FODMAP)-based diet types can also be beneficial for patients. The main food intolerance types seen are lactose intolerance, gluten (wheat) intolerance, favism and fructose intolerance, which develop due to enzyme deficiency (enzymatic-based). Apart from all these, food intolerance can be seen in individuals due to pharmacological (drug components in food) or idiopathic reasons such as dopamine and histamine. Some colorants, nitrate, nitrite and monosodium glutamate from food additives cause idiopathic food intolerance. In this study, scientific studies on early diagnosis and current dietary approaches in the increasing prevalence of food intolerance were compiled. Keywords: Food intolerance, Diet, FODMAP
Keywords: Eren A. G. , Güneş Bayır A., -NUTRITIONAL APPROACHES IN FOOD INTOLERANCES-, 3rd International Conference on Scientific Research, Adana, Türkiye, 3 - 05 Ocak 2022, cilt.1, ss.1